Understanding the impact of wood type and moisture on the bonding strength of glued wood. Issue 1 (2nd January 2023) - Li, Wanzhao; Liu, Chuhang; Wang, Xinzhou; Shi, Jiangtao; Mei, Changtong; Van den Bulcke, Jan; Van Acker, Joris
ABSTRACT: The bonding strength of glued wood is strongly related to wood type and environmental conditions, and this relationship is a dynamic variable. It is thus important to investigate the effect of wood type and relative humidity (RH) on the bonding strength using dynamic tests. Two-layered plywood was lab produced, and two sides of the bonding interphase were latewood and earlywood. After conditioning the samples at 60%, 80%, and 95% RH, the bonding strength was measured with a universal mechanical test machine, and strain distribution was recorded simultaneously with digital image correlation (DIC). The results show that bonding strength and deformation increased with an increase in RH. The moisture content (MC) in the latewood was more than that in the earlywood. This decreased the difference in stiffness between latewood and earlywood and led to a more homogeneous strain distribution. This can protect earlywood from failure caused by larger local structural ruptures. Large strain in latewood contributed to high bonding strength. For all samples, failure occurred in the glue line or on the side with earlywood only. For samples failing in the glue line, structural ruptures occurred in the bonding interphase and the wood next to the bonding interphase.